International experience in drug assessment for rare diseases: flexibility of approaches - K. S. Radaeva; A. S. Kolbin (Реальная клиническая практика: данные и доказательства, 2024)
Relevance. The regulation of orphan drugs plays a key role in the development of medicines for rare diseases that affect only a small percentage of the population. This specialized regulatory framework is designed to encourage pharmaceutical companies to allocate resources to the development of drugs for diseases that might otherwise be overlooked due to limited commercial appeal. Experts from Cogentia Healthcare Consulting Ltd. analyzed trends in the assessment of orphan drugs in the UK.Objective. The aim of this work was to analyze and present the main trends in the optimization of decision-making regarding orphan drugs based on the data of an analysis conducted by the experts of Cogentia Healthcare Consulting Ltd.Results. Regulatory bodies have shown some flexibility in the assessment of orphan drugs and have used approaches designed to address uncertainties in the evidence, accepting, in some cases, low-quality evidence, expert opinion and evidence from real-world clinical practice and applying more flexible pharmacoeconomic approaches. However, despite the existing assumptions, the evaluation process for orphan drugs often takes longer than that for non-orphan drugs.Conclusions. Although different approaches to market regulation for orphan drugs have helped stimulate their development worldwide and address unmet medical needs, delays in decision-making for orphan drugs have seriously affected their availability to patients in need.